State of subversion
1 online resource (1 volume)
Keywords: This volume looks at the interface between ideology, religion and culture in Punjab in the 20th century, spanning from colonial to post-colonial times. Through a rereading of the history of Punjab and of Punjabi migrant networks the world over, it interrogates the term radicalism' and its relationship with terms such as militancy', terrorism' and extremism' in the context of Punjab and elsewhere during the period; explores the relationship between left and religious radicalism -- such as the Ghadar movement and the Akalis -- and the continuing role of radical movements from British Punjab to the independent states of India and Pakistan.Expanding the dimensions on the study of Punjab and its historical impact in the South Asian region, this book will interest scholars and students of modern Indian history, politics and sociology.